2003
DOI: 10.1038/sj.cdd.4401208
|View full text |Cite
|
Sign up to set email alerts
|

NRADD, a novel membrane protein with a death domain involved in mediating apoptosis in response to ER stress

Abstract: NRADD (neurotrophin receptor alike death domain protein) is a novel protein with transmembrane and cytoplasmic regions highly homologous to death receptors, particularly p75 NTR . However, the short N-terminal domain is unique. Expression of NRADD induced apoptosis in a number of cell lines. The apoptotic mechanism involved the activation of caspase-8 and execution of apoptosis without requiring mitochondrial components. The activation of this death receptor-like mechanism required the N-terminal domain, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 33 publications
1
31
0
Order By: Relevance
“…Mus musculus (m), Homo sapiens (h), *the catalytic part of the hypothetical fulllength human pseudo-caspase-12 was used tunicamycin and brefeldin A) in ST14A and Schwann cells. 12 Taken together, the results reported for Bap31, NRADD and caspase-8 suggest that caspase-8 may be another ERstress-associated protease. 12 In support of an important role for caspase-8 in ER stress is the observation that caspase-8 deficiency significantly delays the onset of tunicamycininduced DNA fragmentation, while caspase-12 deficiency hardly has any effect on both DNA fragmentation and caspase activation.…”
Section: Is Caspase-12 Implicated In Apoptosis?mentioning
confidence: 68%
See 3 more Smart Citations
“…Mus musculus (m), Homo sapiens (h), *the catalytic part of the hypothetical fulllength human pseudo-caspase-12 was used tunicamycin and brefeldin A) in ST14A and Schwann cells. 12 Taken together, the results reported for Bap31, NRADD and caspase-8 suggest that caspase-8 may be another ERstress-associated protease. 12 In support of an important role for caspase-8 in ER stress is the observation that caspase-8 deficiency significantly delays the onset of tunicamycininduced DNA fragmentation, while caspase-12 deficiency hardly has any effect on both DNA fragmentation and caspase activation.…”
Section: Is Caspase-12 Implicated In Apoptosis?mentioning
confidence: 68%
“…12 Taken together, the results reported for Bap31, NRADD and caspase-8 suggest that caspase-8 may be another ERstress-associated protease. 12 In support of an important role for caspase-8 in ER stress is the observation that caspase-8 deficiency significantly delays the onset of tunicamycininduced DNA fragmentation, while caspase-12 deficiency hardly has any effect on both DNA fragmentation and caspase activation. 18 Nevertheless, the exact roles of these proapoptotic factors during ER-stress-induced apoptosis need further investigation.…”
Section: Is Caspase-12 Implicated In Apoptosis?mentioning
confidence: 68%
See 2 more Smart Citations
“…These results support observations made by others that AS-ODNs targeted to the region of the translational start site are likely to be effective in suppressing translational initiation (Higgins, Perez et al 1993;Reed 1997;Dias and Stein 2002). However, a BLAST search of the AS-ODN11 sequence revealed that, as well as being complementary to position 11-27 of Lcn2, it is also complementary to position 702-719 of the mRNA that encodes Nradd (Neurotrophin receptor associated death domain, GeneID: #67169, NM_026012), a death domain protein (Wang, Shao et al 2003;Gowrishankar, Zeidler et al 2004). Thus, the effect of AS-ODN11 on Lcn2 expression could be an indirect consequence of the inhibition of Nradd production due to a primary antisense effect on the level of Nradd mRNA.…”
Section: Discussionmentioning
confidence: 99%